China's Detonation-driven Shock Tube Wind Tunnels: A Case Study of Transnational Science in Aeronautics during the Cold War. Issue 3 (3rd July 2021) - Zhihu, Zhang; Seely, Bruce E.
Abstract : Abstract From the perspective of the history of technology, this paper reviews the development of a hypersonic wind tunnel in China. The key figure is Yu Hongru 俞鸿儒, who began his research into shock tube wind tunnels in the 1950s, and proposed ways to use detonation driver technology. His insight, however, was stymied during China's "Cultural Revolution." After China's reform and opening-up began in the late 1970s, Yu 俞 designed a hypersonic tunnel driven by backward hydrogen-oxygen detonation utilizing a dumping section and carried out verification experiments with RWTH Aachen University. After 2000, the high-temperature gas dynamics team of the Institute of Mechanics of the Chinese Academy of Sciences built the first long test-duration detonation-driven shock tunnel. This case study draws extensively upon Chinese literature, documents, and interviews. It adds to the history exploring Cold War science and technology. While much research has focused on activities in the USA and the USSR, this article contributes to the less-explored history of scientific research and development in China after 1950, demonstrating the importance of knowledge flows within the wider concept of Cold War transnational science. In addition, this transnational emphasis contributes a non-western chapter to the western-centric history of aerospace technology development.